The Ugi four-component reaction enables expedient synthesis and comparison of photoaffinity probes - Bush, J; Walport, L; McGouran, J; Leung, I; Berridge, G; van Berkel, S; Basak, A; Kessler, B; Schofield, C (2013)
Photoaffinity probes are increasingly being used for the study of biological interactions; however, the lack of structure-activity relationship studies has hindered their rational application. We describe the use of the Ugi four-component reaction (U-4CR) for the expedient and versatile assembly of photoaffinity scaffolds that can be linked to small molecule probes. The rates, yields and sites of crosslinking of five commonly used photoreactive groups comprising diazirines, aryl azides and a benzophenone, were compared using a human 2-oxoglutarate oxygenase as a model protein. The results reveal significant differences in the behavior of the probes and suggest that empirically guided optimization of probes for specific tasks is desirable. In the absence of such optimization it may be advisable to use a set of crosslinking probes/conditions; the U-4CR provides a convenient method for obtaining such a set. This journal is © The Royal Society of Chemistry 2013.